Natural durability and chemical composition of the Liquidambar sp. wood - Freitas, Thais Pereira; Benigno Paes, Juarez; da Silva Oliveira, José Tarcísio; Torezani Neto Boschetti, Walter; Nava Soratoo, Déborah; Silva de Jesus, Márcia (Floresta, 2020)
The wood is a material of biological origin and because of its chemical composition is subject to the attack of various organisms that use it as a source of food. Thus, this study aimed to evaluate the natural durability and chemical composition of the Liquidambar sp. wood. Were performed the accelerated laboratory test, with a pure culture of the Postia placenta fungus, causer of brown rot , and no choice-feeding of termites Nasutitermes corniger. After both tests, the samples were dried in an oven at 103 ± 2ºC until reaching constant mass and later weighed, to evaluate the percentage of mass loss. The contents of extractives, soluble, insoluble and total lignin, and holocellulose were also determined. The studied wood obtained losses of mass of 37.79% and 23.37%, when submitted to the action of fungus and termites, respectively, and an average extractive content equal to 4.13%. It is concluded that the Liquidambar sp. wood was moderate resistance to the attack of the brown rot fungus, and little resistant to the action of employed termites.